The Libri sententiarum potestatis Mediolani (1385-1429): a first codicological and diplomatistic analysis (Studi di storia medioevale e di diplomatica - Nuova Serie, 2023)
The series of Libri sententiarum potestatis Mediolani contains the criminal verdicts sentenced by the podestas of the city between the years 1385 and 1429 (despite some gaps) and represents with no doubt a fundamental source, especially considering the terrible conditions of the medieval milanese documentary material. The edition of its first register has awakened the interest towards these documents, poorly considered by historiography for a long time, and the current analysis of both diplomatistic and codicological aspects of the series allowed to detect its peculiarities, while showing them as the reflection of widely shared notarial practices. It also highlighted which factors remained constant through the series and which ones changed over time, as well as it opened the door for potential research prospects in the future.
Keywords: Milan; Visconti; criminal justice; podestas; manuscripts